2020
DOI: 10.1186/s12947-020-00189-z
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of three-dimensional echocardiography for evaluating left atrial function in patients with coronary slow flow phenomenon: a case control study

Abstract: Background: Coronary slow flow phenomenon (CSFP) involves the delayed opacification of the coronary distal vessel, in the absence of an obstructive lesion in the epicardial coronary artery during angiography. Since the link between left atrial (LA) function and decreased left ventricular function is still unclear, we evaluated LA function using real-time three-dimensional echocardiography (RT3DE) in patients with CSFP, and subsequently determined the incremental value of RT3DE. Methods: This study enrolled 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Altered LA volume and function are also associated with CSFP. Li jun et al [38] noted that decreased LA systolic function in patients with CSFP was related to decreased coronary flow velocities and the number of involved arteries. Another small study noted that CSFP was linked to increased LA volume, impaired LA reserve function, and enhanced systolic function [39].…”
Section: Discussionmentioning
confidence: 99%
“…Altered LA volume and function are also associated with CSFP. Li jun et al [38] noted that decreased LA systolic function in patients with CSFP was related to decreased coronary flow velocities and the number of involved arteries. Another small study noted that CSFP was linked to increased LA volume, impaired LA reserve function, and enhanced systolic function [39].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the author with the most publications was Chun-Yan Ma from China. The studies of her team have mainly concentrated on the novel echocardiography-based technique to assess CSF and gene polymorphisms in the pathogenesis of CSF [ 8 , 9 ]. Six of the top 15 authors by publications on CSF were from Turkey, and some authors had very close co-operative relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of CSFP on left atrial function has been minimally investigated. A few studies can be found in the existing literature, but the conclusion is controversial [38,39]. Left atrium plays an important role in ensuring proper performance of left ventricular function and the systemic circulation.…”
Section: Csfp and Left Atrial Functionmentioning
confidence: 99%